PENERAPAN POLA ASUH OTORITER TERHADAP ANAK REMAJA DALAM PROSES BERKELUARGA - Rahman Hakim, Noval; Wanidha Andriani, Viena; Qori'ah, Maria (AL IHSAN: Jurnal Pendidikan Islam Anak Usia Dini, 2023)
Abstract Parents have an obligation to guide, direct and educate children. Therefore, parents must take care to raise and prepare for the future to come. Authoritarian parenting is a way in which parents educate children to continue to obey, not argue and to follow the directions that have been strictly determined by the parents. In this article, we will review the authoritarian parenting style of teenagers in the process of starting a family, where daily life activities are carried out firmly and swiftly, with obedience that must be carried out in starting a family. This research is a type of literature review research. Authoritarian parenting in adolescents is a parental method in which adolescent children are required to be bound by the rules applied within the family sphere. Adolescents are individuals aged 10-19 years who are divided into two terminations, namely early adolescents in the age range 10-14 years and late adolescents 15-19 years. Family is a small group in society consists of father, mother and children. Kata Kunci: Authoritarian Parenting, Teengers, Having A Family